Optimizing DNA extraction protocols for the diet analysis of a baleen whale (Eubalaena australis) ... - Parikh, Aashi; O'Rorke, Richard; Carroll, Emma; Vermeulen, Els; Harcourt, Robert; Chariton, Anthony (Zenodo, 2024)
Faecal metabarcoding is widely used for mammalian diet analysis. However, most extraction protocols are designed to use high molecular weight genomic DNA, making short sequences of digested DNA challenging to extract. Here, we compared a phosphate buffer DNA extraction method along with two commercial extraction kits (the QIAamp Fast DNA Stool Mini Kit and the PowerSoil kit) with the following variations: 1) different durations of incubation in a phosphate buffer (1 hour and 24 hours), 2) processing of both pellet and supernatant from phosphate buffer incubation, and 3) two different concentrations of DNA binding buffer to examine prey DNA in southern right whale (Eubalaena australis, SRW) faecal matter. We found that the choice of extraction protocol influenced richness, diversity, and composition of eukaryotes (18S rDNA) and crustaceans (Crust16S mtDNA) detected in SRW faecal samples. The PowerSoil protocol performed well for both markers, delivering the highest target richness for 18S rDNA and highest ... : Southern right whale faecal samples were collected opportunistically over decades of research. Faecal samples underwent DNA extraction using three different methods (phosphate buffer extraction, PowerSoil kit and QIAamp FAST DNA Stool Mini Kit) with modifications in each leading to 12 unique protocols. The modifications included: incubating samples for 1 hr and 24 hrs in a phosphate buffer, processing both the pellet and supernatant from phosphate buffer incubation, and the addition of 1x and 2x DNA binding buffer to the silica column. Extracted samples were amplified via a universal 18S and crustacean-specific 16S marker and sequenced. Analyses for taxonomic richness, diversity, and composition were performed in R to compare results from the different protocols. ...